2015
DOI: 10.1152/ajpgi.00172.2015
|View full text |Cite
|
Sign up to set email alerts
|

Lack of soluble fiber drives diet-induced adiposity in mice

Abstract: Diet-induced obesity is often modeled by comparing mice fed high-fat diet (HFD), which is made from purified ingredients, vs. normal chow diet (NCD), which is a low-fat assemblage of relatively unrefined plant and animal products. The mechanism by which HFD promotes adiposity is complex but thought to involve low-grade inflammation and altered gut microbiota. The goal of this study was to investigate the extent to which HFD-induced adiposity is driven by fat content vs. other factors that differentiate HFD vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
175
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(193 citation statements)
references
References 24 publications
18
175
0
Order By: Relevance
“…For example, Martens and colleagues observed that lack of fiber resulted in microbiota consuming the mucus layer, which made the intestine more prone to attack by invasive pathogens [21]. We observed that lack of fermentable fibers results in greatly reduced epithelial cell proliferation that leads to a thin mucosa in which but bacteria readily encroach [22,23]. Such effects on host-microbiota interaction promoted low-grade inflammation that underlined a significant portion of metabolic syndrome induced by HFD, which is generally devoid of fermentable fiber, and were sufficient to promote a significant degree of adiposity even in the context of a low-fat diet [22,23].…”
Section: Fiber: Needed For Health But Type Amount and Context Mattermentioning
confidence: 86%
See 3 more Smart Citations
“…For example, Martens and colleagues observed that lack of fiber resulted in microbiota consuming the mucus layer, which made the intestine more prone to attack by invasive pathogens [21]. We observed that lack of fermentable fibers results in greatly reduced epithelial cell proliferation that leads to a thin mucosa in which but bacteria readily encroach [22,23]. Such effects on host-microbiota interaction promoted low-grade inflammation that underlined a significant portion of metabolic syndrome induced by HFD, which is generally devoid of fermentable fiber, and were sufficient to promote a significant degree of adiposity even in the context of a low-fat diet [22,23].…”
Section: Fiber: Needed For Health But Type Amount and Context Mattermentioning
confidence: 86%
“…We observed that lack of fermentable fibers results in greatly reduced epithelial cell proliferation that leads to a thin mucosa in which but bacteria readily encroach [22,23]. Such effects on host-microbiota interaction promoted low-grade inflammation that underlined a significant portion of metabolic syndrome induced by HFD, which is generally devoid of fermentable fiber, and were sufficient to promote a significant degree of adiposity even in the context of a low-fat diet [22,23]. Conversely, supplementing HFD with the fermentable fiber inulin but not the insoluble fiber cellulose resulted in a microbiota-dependent fortification of the mucosa that prevented microbiota encroachment and protected against HFD-induced metabolic syndrome [22,23].…”
Section: Fiber: Needed For Health But Type Amount and Context Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…However, several other dietary factors could be contributing. An animal study demonstrated that changes in microbiota leading to intestinal inflammation were caused by the lack of fermentable fiber, and not by the content of fat in the diet [68]. When mice were fed a diet that induced metabolic endotoxemia, adding a prebiotic improved metabolic markers [69].…”
Section: Other Components Of the Western Diet That Influence Inflammamentioning
confidence: 99%